# Which expressions are equivalent to this expression? 3(n+4) 3n+4 12+n+n+n 3n−12 2n+12+n WILL MEDAL!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

Answer: We will start by expanding (or multiplying through) with 3(n+4)

We get:
3n + 12
3n can be expanded to equal 2n+n, so the correct answer will be
2n + 12 + n

Simply add the options together and see what one matches 3n + 12

2n + 12 + n = 3n + 12, which in turn equals 3(n+4)

ANSWER: 2n + 12 + n

12+n+n+n

2n+12+n

Step-by-step explanation:

I took the test on K12 and this was the right answer

## Related Questions

Find the factor. 5y^2+4y-1=(5y-10)(___)

5y^2+4y-1
= 5y^2 + 5y - y - 1
= 5y(y+1) - 1(y+1)
= (y+1)(5y -1) or
= (5y-1)(y +1)

(5y-1)(y +1)

A rational expression is undefined when the denominator is zero true or false ?

The answer is true, any time the denominator of a rational expression is 0, it is undefined. A rational expression is something that can be written as x/y, where x and y are both integers and y is not equal to zero. The denominators 0 are expressly prohibited by this notion of a reasonable expression.

What is a rational Expression?

Variable-filled fractions are rational expressions. Basis functions are used as the numerator and the denominator in rational expressions.

To put it another way, it has the format p(x)/q(x), where q(x) 0 and p(x) and q(x) are polynomials.

Because rational expressions are really fractions, we can treat them in the same manner as fractions.

To know more about the rational expression:

brainly.com/question/19585906

#SPJ2

True A rational expression is undefined whenever its denominator is zero. By definition, a rational expression is an expression that can be in the form x/y where x and y are integers and y is not equal to zero. This definition of a rational expression strictly excludes denominators of zero.

What is the solution to the equation fraction 4 over 5 n minus fraction 1 over 5 equals fraction 2 over 5 n?

n = 0.5

Step-by-step explanation:

Equation according to given data:

(4/5)n - 1/5 = (2/5)n

Solution:

(4/5)n - 1/5 = (2/5)n

Subtracting (4/5)n on both sides of equation:

= (4/5)n - 1/5 - (4/5)n = (2/5)n - (4/5)n

= - 1/5 = -2/5n

Multiplying -5/2 on both sides of equation:

= -1/5 . -5/2 = -2/5n . -5/2

= 5/10 = n

= n= 1/2 = 0.5

Equation: (4/5)n - 1/5 = (2/5)n

Steps:

1. ((4/5)n - 1/5) - (4/5)n = ((2/5)n) - (4/5)n

2. -1/5 = -2/5n

3. -1/5/-2.5 = -2/5n/-2.5

Solution: n = 2/25 or 0.08

A copy machine makes 24 copies per minute. How long does it take to make 114 copies?